2019
DOI: 10.1177/2047487319856448
|View full text |Cite
|
Sign up to set email alerts
|

Restoring pulsatility and peakVO2 in the era of continuous flow, fixed pump speed, left ventricular assist devices: ‘A hypothesis of pump's or patient's speed?’

Abstract: Despite significant improvement in survival and functional capacity after continuous flow left ventricular assist device implantation, the patient's quality of life may remain limited by complications such as aortic valve insufficiency, thromboembolic episodes and gastrointestinal bleeding attributed to high shear stress continuous flow with attenuated or absence of pulsatile flow and by a reduced peak oxygen consumption (peakVO2) primarily associated with a fixed pump speed operation. Revision of current evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…An overview on the effect of LVAD speed increase on peak exercise was reported by Laoutaris . In two studies a positive increase in peak oxygen consumption was found, 11 studies reported moderate increase within the range of 7–9%, two studies reported little or no effect on TCO and five studies did not observe significant differences in oxygen consumption at peak exercise.…”
Section: Effects Of Lvad Speed Increase In Different Exercise Profilesmentioning
confidence: 95%
“…An overview on the effect of LVAD speed increase on peak exercise was reported by Laoutaris . In two studies a positive increase in peak oxygen consumption was found, 11 studies reported moderate increase within the range of 7–9%, two studies reported little or no effect on TCO and five studies did not observe significant differences in oxygen consumption at peak exercise.…”
Section: Effects Of Lvad Speed Increase In Different Exercise Profilesmentioning
confidence: 95%
“…Due to the still unclear picture of maximal and submaximal exercise tests, pre-and/or post-LVAD implantation, further studies have been conducted (34,39,40). Exercise test results and their potential for risk stratification would provide important clinical insights (17,21,41).…”
Section: Submaximal Vs Maximal Exercisementioning
confidence: 99%
“…This objective constitutes a compromise function that aims for ventricular unloading and ensures the opening of the aortic valve. A permanent closure of the aortic valve may lead to fusion of the aortic valvular cusps and a resulting thrombus formation [10]. By ventricular unloading we refer to reducing the hydraulic work that the LV has to perform in order to provide sufficient perfusion.…”
Section: Optimal Control Problem Formulationmentioning
confidence: 99%